Breeding of a xylose-fermenting hybrid strain by mating genetically engineered haploid strains derived from industrial Saccharomyces cerevisiae. (1st December 2014) - Inoue, Hiroyuki; Hashimoto, Seitaro; Matsushika, Akinori; Watanabe, Seiya; Sawayama, Shigeki
Abstract: The industrial Saccharomyces cerevisiae IR-2 is a promising host strain to genetically engineer xylose-utilizing yeasts for ethanol fermentation from lignocellulosic hydrolysates. Two IR-2-based haploid strains were selected based upon the rate of xylulose fermentation, and hybrids were obtained by mating recombinant haploid strains harboring heterogeneous xylose dehydrogenase (XDH) (wild-type NAD + -dependent XDH or engineered NADP + -dependent XDH, ARSdR), xylose reductase (XR) and xylulose kinase (XK) genes. ARSdR in the hybrids selected for growth rates on yeast extract-peptone-dextrose (YPD) agar and YP-xylose agar plates typically had a higher activity than NAD + -dependent XDH. Furthermore, the xylose-fermenting performance of the hybrid strain SE12 with the same level of heterogeneous XDH activity was similar to that of a recombinant strain of IR-2 harboring a single set of genes, XR/ARSdR/XK. These results suggest not only that the recombinant haploid strains retain the appropriate genetic background of IR-2 for ethanol production from xylose but also that ARSdR is preferable for xylose fermentation.